Upaya Penegakan Emansipasi Wanita melalui Optimalisasi Pembangunan Gender dengan Metode Regresi Panel - Phalufi, Inu Alifiyah; Alya Hartarie, Raden Nabila; Novitriani, Ellena; Widodo, Edy (Indonesian Journal of Applied Statistics, 2022)
The role of women nowadays is no different from the men, only to a reasonable extent. The role of women's emancipation itself has been upheld in Indonesia, as those who will be the spearheads in family education for their children that must have broad skills and insights. The Human Development Index (HDI) is mostly becoming an important index as a measurement of the success level in quality of human life (community) building efforts. By conducting an analysis using the panel regression method in the Regency / City of West Sulawesi (as a province in Indonesia that has the 4th lowest HDI score) to find out how much women's participation can affect the level of quality of life in Indonesia and as an evaluation of which components must be improved by government for the next period in the welfare of its people. This analysis concludes that the Mamuju regency is known as the region that contributes the largest weight to the increase in GDI while the Pasangkayu regency contributes the lowest weight to the increase in GDI so that the government should make the development of supporting facilities for community welfare more equitable.Keywords : GDI, Woman Emancipation, Panel Regression